The Effect of a Culturally Responsive Teaching Approach Integrated with Comics with the Think Talk Write Learning Model on Students’ Learning Activities and Achievement in Basic Law of Chemistry Topics - Afifah Khoirunnisa; Bakti Mulyani; Elfi Susanti Vh; Sri Yamtinah; Mohammad Masykuri; Maria Ulfa; Ari Syahidul Shidiq (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
This study examines the impact of integrating the Culturally Responsive Teaching (CRT) approach with comic-based learning and the Think Talk Write (TTW) model on student learning activities and achievements in fundamental chemistry. Focusing on chemical reactions (combustion, rusting, fermentation, etc.) and laws (Dalton’s, Proust’s, Gay-Lussac’s, etc.), the research adopts a pretest-posttest non-equivalent control group design in a quasi-experimental setting with 36 students divided equally between control and experimental groups. Comparative analysis shows that the experimental group outperforms the control group in learning activities and achievements. The experimental group, subjected to the CRT and TTW model, demonstrates significantly higher engagement in learning activities. The N-Gain Score test reveals a notable increase in learning effectiveness—56.40% for the experimental group versus 29.69% for the control group, indicating the latter's relative ineffectiveness. In learning achievement, the experimental group exhibits a considerable improvement of 67.20%, while the control group shows a moderate gain of 50.12%. The results of the Multivariate Analysis of Variance (MANOVA) test, with the positive effect of integrating CRT with comics and the TTW model on student learning activities and achievements. The study highlights the efficacy of this approach in enhancing students' understanding and engagement in chemistry, suggesting a promising direction for future educational practices.